THE INFLUENCE OF MOTIVATION, COMPETENCE AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE - Nandrang, Rosdiana; Hasanuddin, Bakri; Mahardiana, Lina (Master of Management Study Program, Faculty of Economics and Business, Tadulako University, 2025)
The purpose of this study was to test and explain empirically (1) Motivation, competence and work discipline have a significant effect on employee performance at the Tojo Una-Una Regency Regional Civil Service and Human Resources Development Agency (2) Motivation has a significant effect on employee performance at the Tojo Una-Una Regency Regional Civil Service and Human Resources Development Agency (3) Competence has a significant effect on employee performance at the Tojo Una-Una Regency Regional Civil Service and Human Resources Development Agency (4) Work discipline has a significant effect on employee performance at the Tojo Una-Una Regency Regional Civil Service and Human Resources Development Agency. The type of research used in this study is causality research. Hypothesis testing using Multiple Linear Regression Analysis with a sample of 64 respondents consisting of 40 civil servants and 24 non-civil servants. The results of the analysis show that (1) Motivation, competence and work discipline have a significant effect on employee performance at the Staffing Agency and Regional Human Resources Development of Tojo Una-Una Regency (2) Motivation has a significant effect on employee performance at the Tojo Una-Una Regency Regional Civil Service and Human Resources Development Agency (3) Competence has a significant effect on employee performance at the Tojo Una-Una Regency Regional Civil Service and Human Resources Development Agency (4) Work discipline has a significant effect on employee performance at the Tojo Una-Una Regency Regional Civil Service and Human Resources Development Agency.